Clinical and microbiological characteristics of healthcare-associated infections in a tertiary care pediatric hospital - Rasha H. Hassan; Heba Eldegla; Fikry Elmorsy; Waleed M. Eldars (SpringerOpen, 2017)
Background and aim: Healthcare-associated infections (HAIs) are an important cause of prolonged hospital stay. This study was conducted to assess the incidence, causative organisms and risk factors of HAIs in pediatric patients. Subjects and methods: Our study was a prospective evaluation of Healthcare-associated infections (HAI) in patients admitted to Mansoura University Children's Hospital, Mansoura, Egypt over a period of one year. Results: Five-hundred twenty-nine patients were included in the study. The overall rate of HAI was 5.2/100 admissions. Infection rates were highest in Pediatric ICU (25.9/100 admissions). The most frequent sites of HAI in our study were BSI (154 cultures; 33.3%), UTI (152 cultures; 32.9%), and VAP (90 cultures;19.5%). Gram negative bacteria were the most common bacteria isolated from positive cultures (47.6% of total 462 positive cultures) and were found to be multidrug resistant bacteria. A high prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) was found. Candida species were the commonest pathogens causing urinary tract infection (UTI). Mechanical ventilation, invasive device utilization, neonatal age, neutropenia, ICU residence and hospital stay for > 7 days were the risk factors significantly associated with HAI in our hospital. We found also, multiple antibiotic therapy usage, beta lactam usage, and ICU residence to be significant risk factors for infection by multidrug resistant pathogens. Conclusion: HAI is a significant problem. We recommend further nationwide multicenter studies to identify the commonest infectious pathogens, antibiotic resistance pattern, and to identify risk factors and pattern of antibiotic usage to overcome multidrug resistance.